Development of wireless passive water quality catchment monitoring system - Muhammad Aznil, Ab Aziz; M. F., Abas; A. A. N., Faudzi; N., Md. Saad; Addie Irawan, Hashim (UTeM, 2018)
To maintain the quality of aquatic ecosystems, good water quality is needed. The quality of water needs to be tracked in real-time for environmental protection and tracking pollution sources. This paper aims to describe the development and data acquired for water catchment quality monitoring by using a passive system which includes location tagging. Wireless Passive Water Quality Catchment Monitoring (WPWQCM) System is used to check and monitor water quality continuously. The condition of water in terms of acidity, temperature and light intensity needs to be monitored. WPWQCM System featured four sensors which are a temperature sensor, light intensity sensor, pH sensor and GPS tracker that will float in water to collect the data. GPS tracker on passive water catchment monitoring system is a new feature in the system where the location of water can be identified. With the extra feature, water quality can be mapped and in the future, the source of disturbance can be determined. UMP Lake was chosen to check and monitor the water quality. The system used wireless communication by using XBee Pro as a medium of communication between CT-Uno board and PC.